SYSTEM DYNAMICS MODEL TO DECREASE CONGESTION COST USING TRANSIT-ORIENTED DEVELOPMENT - Suryani, Erma; Hendrawan, Rully Agus; Mukti, Faiz Anggoro; Az- Zahra, Alifia (MATTER: International Journal of Science and Technology, 2020)
Traffic congestion has had an impact on longer travel time and increased operational costs because vehicle speeds do not reach the speeds designed. Therefore, this research aims to decrease congestion costs using transit-oriented development (TOD). TOD is the integration of land use and transit to create a community that can walk within walking distance of a transit stop or station. It integrates people, jobs, and services to create efficient, safe, and comfortable services for traveling on foot or by bicycle, transit, or car. TOD can reduce the congestion cost by encouraging housing locations near transit facilities, incorporating retail into regional development to attract customers from both TOD and main roads, as well as improving compatibility and connectivity of transportation systems. As a method used to reduce the congestion cost, we utilized the system dynamics (SD) simulation model based on the consideration that SD can accommodate the complexity of the dynamics of several variables influencing the cost of traffic congestion. SD provides a framework to develop a causal loop diagram that allows SD as a tool to test the impact of various strategies and policies that affect the cost of traffic congestion. Some important factors that affect the cost of traffic congestion are congestion time per day and gross domestic product per capita. Simulation results of the scenario model after implementing the TOD show that the congestion cost per hour per capita is projected to decrease by an average difference of 53%. Congestion costs after applying TOD are projected to be around IDR 2025 per hour per capita in 2021 and IDR 451,800 per hour per capita in 2045